Pengembangan E-Modul Berbasis Flipbook Materi Manusia dan Lingkungan - Herlinda Rahayu Riskynianyo; Lina Novita; Tustiyana Windiyani (Departement of Mathematics Education, 2024)
The This study aims to produce and develop flipbook-based e-module products on human and environmental materials in class V SDN Nambo 02 Bogor district and to determine the feasibility of the developed flipbook-based e-module. This developer uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research begins with needs analysis, creating e-modules, then developing e-modules, then validating by experts, revising the product, then conducting limited trials (implementing) flipbook-based e-modules to predetermined respondents. The average total validation score from material experts, media experts, and linguists shows that flipbook-based e-modules are very usable with an average percentage gain of 99.33%. In the limited test phase, 30 students gave very good responses with an average percentage of 94.20% of the flipbook-based e-module used. According to the results of the research concluded, this flipbook-based e-module has been tested, interesting, interactive and very appropriate for students to use for learning.